Analysis of Experts' Opinion on the Human Excretory System Model for Teaching Biology in Nigeria - Ebenezer Omolafe Babalola; Desire Adunola Ayoola; Eyiyemi Veronica Omolafe (Universitas Pendidikan Indonesia (UPI), 2023)
To establish the accuracy and usability of the instructional model, it must be verified by experts in the area of the subject content. The model of the human excretory system (MHES) has to be examined and verified by a qualified Biology education expert to ascertain its accuracy while the usability has to be verified by an educational technology expert. Hence, it is needed to determine the experts’ validation of MHES before it can be used to teach a Biology concept. Descriptive research of the survey type was adopted for this study. The sample for this study comprised three educational technology experts from the Department of Educational Technology and three Biology education experts from the Department of Science Education, University of Ilorin, Nigeria. Two instruments were developed for the study: Educational Technology Experts’ Rating Scale and Biology Education Experts’ Rating Scale. Descriptive statistics of the mean score and standard deviation were used to analyze the research questions. The findings of this study revealed the experts’ overall assessment of the effectiveness of the model for instruction was high, suitable, and found to be adequate. Based on the findings of this study, it is concluded that the developed MHES can be used to enhance Biology students’ academic performance on the topic human excretory system